“Los factores motivacionales y su incidencia en el desempeño laboral del personal del GAD municipal del cantón La Maná, provincia de Cotopaxi, año 2020”. - Arévalo Matamoros, Thalía Lilibeth (2020)
The present research work aimed to determine the motivational factors and their incidence in the work performance of the personnel who work in the municipal GAD of the canton La Maná, the same that reverted of great importance, since the work performance had an impact on the results obtained or on the fulfillment of the objectives proposed by the institution. For this, exploratory, descriptive, field and bibliographic research was used, in addition, empirical methods such as deduction, induction, description, analysis and synthesis were used, and supported by dynamic techniques that facilitated the collection of the necessary information, being these, the interview to be carried out with the mayor of the municipal GAD and the survey of employees and workers, whose instrument to be used consisted of a questionnaire of closed questions previously prepared based on the defined variables, in this case job performance and motivational factors that affect it; The population under study was all administrative personnel and workers, made up of a universe of 249 people, of which a significant sample was obtained, after applying a statistical formula that made it easier to establish the number of people to be surveyed. Through the diagnosis, it was possible to conclude that the main motivational factors were the effort to cancel salaries on time, their legal benefits and the opening of the highest authority to dialogue, a high percentage of employees and workers carry out their activities out of obligation, but not out of commitment to the institution. As an alternative proposal, a motivational action plan was suggested to improve the work performance of the activities carried out by employees and workers, with strategies focused on strengthening professional capacities, increasing the commitment of collaborators with the institutional identity, decreasing the levels of stress with activities such as rumba therapy, motivational movie projections. Coming to the conclusion that the most relevant motivational factors in the municipal GAD were the work environment, labor compensation, encouragement for good performance, this explained the initial results of the low level of commitment to the entity. The direct beneficiaries constituted the staff that works in the aforementioned institution and its authorities or directors, the students who carry out the research work and the users of the municipality, while the community in general is the indirect beneficiaries.